Analysis of the Spontaneous Emission Limited Linewidth of an Integrated III–V/SiN Laser (Laser Photonics Rev. 16(6)/2022). Issue 6 (15th June 2022) - Chow, Weng W.; Wan, Yating; Bowers, John E.; Grillot, Frédéric
Abstract : Quantum‐Dot Lasers The maturating of III–V laser technology intensifies the exploration of complex optical configurations based on integrating III–V and silicon photonics. In article number 2100620, Yating Wan and colleagues describe a laser theory, beyond the customary quasi‐mode approximation for treating resonator outcoupling, for understanding the physics underlying spectral narrowing to Hz‐level, spontaneous‐emission limited lasing linewidth. This theory will serve as an analytical tool for parametric studies to produce timely results in engineering design.